Power detectors for integrated microwave/mm-wave imaging systems in mainstream silicon technologies. (April 2016) - Gu, Qun Jane; Li, James C.; Tang, Adrian
Highlights: Analyze the detailed work mechanisms of three detectors for integrated microwave/mm-wave imaging. Provide design procedures and insights for the three detectors. They are CMOS power detectors, bipolar power detectors, and super-regenerative detectors. Defined two FOMs to quantify detectors used in both wideband and narrowband imaging respectively. Abstract: This paper analyzes and compares three different types of detectors, including CMOS power detectors, bipolar power detectors, and super-regenerative detectors, deployed in the literature for integrated microwave/mm-wave imaging systems in mainstream silicon technologies. Each detector has unique working mechanism and demonstrates different behavior with respects to bias conditions, input signal power, as well as bandwidth responses. Two Figure-of-Merits for both wideband and narrowband imaging have been defined to quantify the detector performance comparison. CMOS and Bipolar detectors are good for passive imaging, while super regenerative detectors are superior for active imaging. The analytical results have been verified by both simulation and measurement results. These analyses intend to provide design insights and guidance for integrated microwave/mm-wave imaging power detectors.